Interleukin-33 Contributes Toward Loss of Tolerance by Promoting B-Cell-Activating Factor of the Tumor-Necrosis-Factor Family (BAFF)-Dependent Autoantibody Production - Rose, William A.; Okragly, Angela J.; Hu, Ningjie N.; Daniels, Montanea R.; Martin, Andrea P.; Koh, Yi Ting; Kikly, Kristine; Benschop, Robert J. (Frontiers in Immunology, 2018)
Breaking tolerance is a key event leading to autoimmunity, but the exact mechanisms responsible for this remain uncertain. Here we show that the alarmin IL-33 is able to drive the generation of autoantibodies through induction of the B cell survival factor BAFF. A temporary, short-term increase in IL-33 results in a primary (IgM) response to self-antigens. This transient DNA-specific autoantibody response was dependent on the induction of BAFF. Notably, radiation resistant cells and not myeloid cells such as neutrophils or dendritic cells were the major source of BAFF and were critical in driving the autoantibody response. Chronic exposure to IL-33 elicited dramatic increases in BAFF levels and resulted in elevated number of B and T follicular helper cells as well as germinal center formation. We also observed class-switching from an IgM to an IgG DNA-specific autoantibody response. Collectively, the results provide novel insights into a potential mechanism for breaking immune-tolerance via IL-33-mediated induction of BAFF.